2016
DOI: 10.1371/journal.pone.0169101
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Invasive Group B Streptococcus Serotypes: Implications for Vaccine Development

Abstract: IntroductionThere is a paucity of longitudinal data on the serotype-specific burden of invasive group B Streptococcus (GBS) disease from low-middle income countries, which could inform selection of vaccine epitopes.MethodsFrom 2005 to 2014, infants less than 90 days of age with invasive GBS disease were identified through sentinel laboratory and hospital admission surveillance at Chris Hani Baragwanath Academic Hospital in Soweto, South Africa.ResultsWe identified 820 cases of invasive GBS disease, including 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…This study showed that serotypes Ia (54%), III (20%) and V (16%) were the predominant serotypes which is in concordance with other studies conducted among pregnant women in South Africa [5]. Serotypes Ia and III together accounted for 74% of the colonised population in our study, whilst the 3 dominant serotypes accounted for 90% of all cases.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study showed that serotypes Ia (54%), III (20%) and V (16%) were the predominant serotypes which is in concordance with other studies conducted among pregnant women in South Africa [5]. Serotypes Ia and III together accounted for 74% of the colonised population in our study, whilst the 3 dominant serotypes accounted for 90% of all cases.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in keeping with another South African study which showed that serotype III is the commonest cause of EOD in South Africa, accounting for 41.4% of all cases, whilst serotype Ia accounted for 34.7% of cases [5]. The majority of invasive disease was caused by serotypes Ia, III and V [5]. These 3 serotypes are included in a pentavalent polysaccharide protein conjugate vaccine currently being developed and is in a phase 1 trial [17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this setting, the burden of early-onset neonatal sepsis is estimated as 35.6 per 1000 live births, and 10% of cases are associated with bacteraemia, with GBS being the most commonly identified pathogen [ 8 ]. We have previously reported a high (and largely unchanged) incidence of EOD (1.41; 95% CI: 1.28–1.55) [ 3 , 9 ]. This is most likely attributable to the poor implementation of the risk-based strategy: only 26% of pregnant women with risk factors actually receive IAP timeously [ 10 ].…”
Section: Introductionmentioning
confidence: 99%